Identification of suitable indicators for tracing human faecal contamination and sewage in urban catchments - Ekklesia, Eveline (2014)
Faecal contamination, particularly from human sources, to surface waters poses a threat to public health especially when the surface water is used for water supply and/or for recreational purposes. Faecal indicator bacteria (FIB) have been used widely as surrogates for faecal contamination but were originally developed in temperate climates. FIB are known to experience growth and decay in the environment and therefore their use has been questioned, especially in tropical environments. This has motivated the present study in Singapore, a tropical and highly urbanised country, in which identification of human-related sources is important. This study aimed to suggest sampling protocols, identify suitable tracers as a function of land use and identify evidence of leaking sewers as sources of human faecal and sewage contamination in a highly urbanised catchment. Preliminary data analysis shows that sampling location influences surface water quality and surface water quality parameters have diurnal variations. Therefore, in this study, dry-weather samples were collected hourly over 12 and/or 24 hr at 13 upstream areas with specific land uses: 6 high-density residential, 5 low-density residential, 1 commercial and 1 industrial. A suite of potential tracers which includes FIB, chemical parameters and HF183 is analysed.